Personality traits of traditional entrepreneur and digital entrepreneur: a systematic literature review / Seow, Richard Yeaw Chong - Seow, Richard Yeaw Chong (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2022)
The popularity of digital entrepreneurship as a research stream is gaining scientific traction in recent years courtesy of the role of digitalization in the commercial sphere. It is acknowledged that the personality traits of the entrepreneur play a vital role in the success of entrepreneurship. Since the emergence of the entrepreneurship concept, there have been countless researches on the personality traits of traditional entrepreneurs (TE) and only a handful on the personality traits of digital entrepreneurs (DE). Most scholars offer similar scientific treatment to DE as TE because digital entrepreneurship is a form of entrepreneurship. Some scholars argue that digital entrepreneurship is distinctly different from traditional entrepreneurship, thus, the scientific discovery of the personality traits of DE should be viewed differently. Are DE different from TE in terms of their personality traits? Or are they the same? This paper aims to investigate the differences between the personality traits of TE and DE. A systematic literature review of recent studies on the personality traits of TE and DE is conducted. The result shows that while both TE and DE share certain similar traits like a low score in agreeableness and neuroticism but a high score in openness, conscientiousness, and extraversion, DE scores lower in both neuroticism and conscientiousness dimensions compared to TE. The limited literature on trait differences warrants further research on other trait dimensions between these two breeds of entrepreneurs